Rekonstruksi Hierarki Peraturan Perundang-Undangan Di Indonesia (Reconstruction Of The Hierarchy Of Legislation In Indonesia) - Zaka Firma Aditya; Muhammad Reza Winata (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2018)
The hierarchy of legislation in Indonesia has been amended 4 (four) times, but still contains juridical issues. The most common problems are related to the overlapping of existing rules. Law Number 12 Year 2011 as the guidance of hierarchy of legislation which is considered to improve the probability in the previous law, was also experiencing the same problem. Some of the problems contained in Law 12/2011 are related to the reposition of the People's Consultative Assembly decree (MPR's decree), the unclear position of the ministerial regulations, the state organs regulations, and local regulations of village. Even, as well as the content of the presidential regulation that is considered to be the same as the government regulation. This paper will discuss about (1) the legal historis and legal policy of the hierarchy of legislation in Indonesia and its problems; (2) the reconstruction of the hierarchy of legislation in Indonesia. The results of this paper that the establishment of a hierarchy of legislation in Indonesia has each political law in accordance with the regime at the time. Each hierarchy has its own problems, although the original aim is to discipline and correct the ambiguity of the previous legislation. Thus, the reconstruction of the hierarchy of legislation is important to ensure consistency and harmony of norms at various levels of legislation. The reconstruction in question is to rearrange the hierarchy of legislation by distinguishing between the legislation in the central and regional levels. AbstrakHierarki peraturan perundang-undangan di Indonesia telah diubah sebanyak 4 (empat) kali, namun masih mengandung permasalahan-permasalahan yuridis di dalamnya. Permasalahan yang paling sering terjadi berkaitan dengan tumpang tindihnya aturan-aturan yang ada. UU No. 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan sebagai pedoman hierarki perundang-undangan yang dianggap dapat mengatasi masalah dalam undang-undang sebelumnya, namun juga mengalami masalah yang sama. Beberapa problematika yang ada dalam UU No. 12 Tahun 2011 berkaitan dengan dikembalikannya kedudukan ketetapan MPR, tidak tegasnya kedudukan peraturan menteri, kedudukan peraturan lembaga negara, dan peraturan desa, serta materi muatan peraturan presiden yang dianggap sama dengan peraturan pemerintah. Tulisan ini akan membahas mengenai (1) legal historis dan politik hukum hierarki peraturan perundang-undangan di Indonesia beserta permasalahan-permasalahnnya; dan (2) rekonstruksi hierarki peraturan perundang-undangan di Indonesia. Adapun hasil penulisan ini bahwa pembentukan hierarki peraturan perundang-undangan di Indonesia memiliki politik hukum masing-masing sesuai dengan rezim pemerintahan pada saat itu. Setiap hierarki memiliki problematikanya masing-masing, meskipun tujuan awalnya sama yaitu untuk menertibkan dan memperbaiki kerancuan dari peraturan sebelumnya, sehingga rekonstruksi hierarki peraturan perundang-undangan penting dilakukan agar menjamin konsistensi dan keselarasan norma-norma pada berbagai tingkatan peraturan perundang-undangan. Adapun rekonstruksi yang dimaksud adalah dengan menata kembali hierarki peraturan perundang-undangan dengan membedakannya antara peraturan perundang-undangan tingkat pusat dan tingkat daerah.